Composite beam generally connected: Analytical model. (1st December 2015) - Focacci, Francesco; Foraboschi, Paolo; De Stefano, Mario
Highlights: General analytical model for composite beams. Linear and non-linear connection: inelasticity. Continuous and discrete connection: interlayer and connectors. Model that provides stresses, displacements, and ultimate load. Application to real cases. Abstract: This research has dealt with composite beams, with continuous or discrete connection between the components (laminated, hybrid or sandwich beams), subjected to transverse loads. This paper is devoted to an analytical model for describing the mechanical behavior of composite beams, under no restrictive assumptions on the connection and interaction. The model, which did not exist in the literature, predicts stresses, strains, and displacements due to loads that induce elastic or inelastic behavior in the connection; it may also predict the load that causes the connection to fail. The governing differential equations are expressed in closed-form, and, as such, help comprehend and interpret the structural behavior. The solution of the equations is numerical, and, as such, allows the results to be obtained easily for all kinds of restraints and loads. The paper presents the mathematical formulation and a case study. The application proves that this model is a viable and easy-to-use tool. The model results are also compared to those of a previous analytical model based on assumptions that may seem somewhat restrictive.